Topological network properties of resting-state functional connectivity patterns are associated with metal mixture exposure in adolescents - Invernizzi, Azzurra; Rechtman, Elza; Oluyemi, Kristie; Renzetti, Stefano; Curtin, Paul; Colicino, Elena; Ambrosi, Claudia; Mascaro, Lorella; Patrono, Alessandra; Corbo, Daniele; Cagna, Giuseppa; Gasparotti, Roberto; et al. (Frontiers in Neuroscience, 2023)
Adolescent exposure to neurotoxic metals adversely impacts cognitive, motor, and behavioral development. Few studies have addressed the underlying brain mechanisms of these metal-associated developmental outcomes. Furthermore, metal exposure occurs as a mixture, yet previous studies most often consider impacts of each metal individually. In this cross-sectional study, we investigated the relationship between exposure to neurotoxic metals and topological brain metrics (global and local efficiency) in adolescents. In 193 participants (53% females, ages: 15-25 years) enrolled in the Public Health Impact of Metals Exposure (PHIME) study, we measured concentrations of four metals (manganese, lead, copper and chromium) in multiple biological media (blood, urine, hair, and saliva) and acquired resting-state functional magnetic resonance imaging scans.